2020
DOI: 10.1186/s12947-020-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of pulmonary embolism causing cardiac arrest by combined endobronchial ultrasound and echocardiography

Abstract: Background Pulmonary embolism (PE) is a life-threatening disease difficult to diagnose and manage in severe hemodynamic unstable patients. Transoesophageal echocardiography (TEE) is considered useful to improve diagnosis, but such approach has physical limitations for the interposition of the airways preventing the clear assessment of the left pulmonary artery. Endobronchial ultrasound (EBUS), a recently developed technique carried out using a modified bronchoscope having a small ultrasound convex probe at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This study shows that different manifestations of APE patients show different clinical phenomena under echocardiography, for example, M-type left ventricular wave group shows the movement of ventricular septum and the enlargement of right ventricle, the short-axis section of aorta shows the existence of thrombus at the artery opening, and the long-axis section of left ventricle shows the enlargement of right ventricle, which is basically consistent with the research results of Einarsen et al, 14 indicating that echocardiography has high diagnostic value for APE. Echocardiography, based on ultrasonic echo technology, can obtain the relevant information of anatomical structure of great vessels and cardiac space and then diagnose patients effectively.…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that different manifestations of APE patients show different clinical phenomena under echocardiography, for example, M-type left ventricular wave group shows the movement of ventricular septum and the enlargement of right ventricle, the short-axis section of aorta shows the existence of thrombus at the artery opening, and the long-axis section of left ventricle shows the enlargement of right ventricle, which is basically consistent with the research results of Einarsen et al, 14 indicating that echocardiography has high diagnostic value for APE. Echocardiography, based on ultrasonic echo technology, can obtain the relevant information of anatomical structure of great vessels and cardiac space and then diagnose patients effectively.…”
Section: Discussionsupporting
confidence: 91%
“…Recent case reports describe that EBUS can be used as a primary diagnostic test in critically ill patients who are too unstable to undergo CTPA. This includes a patient in cardiac arrest who improved with intravenous thrombolysis therapy for massive PE diagnosed with bedside EBUS [9], and patients on extracorporeal membrane oxygenation [10]. However, there has yet to be a consensus on the diagnostic…”
Section: Discussionmentioning
confidence: 99%
“…An intraluminal thrombus in the vessels can be easily detected using the colour Doppler mode. However, only few cases of PE diagnosed using EBUS have been reported 11. A study of 32 cases reported that EBUS is comparable to CTA for PE diagnosis 12.…”
Section: Discussionmentioning
confidence: 99%